2016
DOI: 10.1038/am.2016.123
|View full text |Cite
|
Sign up to set email alerts
|

Well-defined polymer microspheres formed by living dispersion polymerization: precisely functionalized crosslinked polymer microspheres from monomers possessing cumulated double bonds

Abstract: The precise method for synthesizing well-defined polymer microspheres via π-allylnickel-catalyzed living coordination polymerization of allene derivatives under dispersion polymerization conditions is described. The π-allylnickel-catalyzed living coordination polymerization of allene derivatives such as phenoxyallene was carried out in protic solvents such as methanol in the presence of stabilizers such as polyvinylpyrrolidone to produce polymer microspheres with a narrowly dispersed diameter distribution (D w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…1 They have become a staple in the modern organic chemists toolbox as a direct result of the myriad of chemical transformations made possible by their unique structure 2,3 and can be found in over 150 natural products, pharmaceuticals 4 , and even elastomers. 5 From a materials context, they are known as "carbon-rich, shape-persistent, axially chiral scaffolds". 6 Yet, their exploration in polymers is limited.…”
Section: Introductionmentioning
confidence: 99%
“…1 They have become a staple in the modern organic chemists toolbox as a direct result of the myriad of chemical transformations made possible by their unique structure 2,3 and can be found in over 150 natural products, pharmaceuticals 4 , and even elastomers. 5 From a materials context, they are known as "carbon-rich, shape-persistent, axially chiral scaffolds". 6 Yet, their exploration in polymers is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Allenes, the simplest class of cumulenes, were discovered over a century ago . They have become a staple in the modern organic chemists toolbox as a direct result of the myriad of chemical transformations made possible by their unique structure , and can be found in over 150 natural products, pharmaceuticals, and even elastomers . From a materials context, they are known as “carbon-rich, shape-persistent, axially chiral scaffolds” .…”
mentioning
confidence: 99%
“…Applications of allene-derived polymers: The applications of allene-derived polymers have been understudied and only a few reports demonstrating tailored morphologies. In 2016, Yamauchi et al used coordination dispersion copolymerization of allenes to synthesize polymer microspheres, using phenoxy-substituted allene as monomer and a diallene as cross-linker . The size of the microspheres was dictated by the identity and concentration of monomer, solvents, and stabilizer (polyvinylpyrrolidone).…”
mentioning
confidence: 99%
“…In 2016, Yamauchi et al used coordination dispersion copolymerization of allenes to synthesize polymer microspheres, using phenoxysubstituted allene as monomer and a diallene as cross-linker. 127 The size of the microspheres was dictated by the identity and concentration of monomer, solvents, and stabilizer (polyvinylpyrrolidone). The authors further demonstrated incorporation of a hydroxyl bearing allene comonomer that was subsequently used for postpolymerization modification, altering the hydrophilicity of the microspheres (Figure 6C).…”
mentioning
confidence: 99%